Increased cisplatin sensitivity of human fibroblasts from a subject with inherent glutathione deficiency - Hansson, J; Edgren, M R; Egyházi, S; Hao, X Y; Mannervik, B; Ringborg, U (Acta oncologica, 1996)
Fibroblasts from an individual with 5-oxoprolinuria are deficient in glutathione (GSH) as compared to cells from a healthy sibling. Glutathione transferase (GST) levels also differ for some isoenzymes: GSH deficient cells have more GST A1-1, but lack GST M1-1. However, the contents of the quantitatively dominating isoenzyme GST P1-1 show no significant difference. While there is equal sensitivity to ultaviolet irradiation (UV), the GSH deficient cells are more sensitive to cisplatin, carboplatin and melphalan. Depletion of GSH with buthionine sulfoximine sensitizes the normal fibroblasts to these drugs. Only slightly more cisplatin-induced DNA cross-links are detected in the GSH deficient cells, and there is no difference in the removal of DNA cross-links. Similar amounts of DNA strand breaks are seen in normal and GSH deficient cells after UV exposure, but there is a reduced rates of resealing of strand breaks in GSH deficient cells. The main conclusion from the studies of these fibroblasts is that GSH plays a significant role in the cellular resistance to cytostatic drugs such as platinum compounds and melphalan.